The Rhetoric of Preaching by Ustadzah Mumpuni Handayayekti in Welcoming the New Hijri Year in Salaman, Magelang - Aenah, Nurul; Najiyah, Nana (Ath Thariq Jurnal Dakwah dan Komunikasi, 2024)
The purpose of this study was to determine the rhetoric of preaching and the planning of preaching of Ustadzah Mumpuni Handayayekti which includes the methods of preaching bil lisan and bil hikmah in Salaman Magelang. This study is a qualitative study with a descriptive approach. The data collected were in the form of words, pictures and results of observations, interviews with sources and documentation which will be interpreted at the data analysis stage. The results of this study indicate that the rhetoric of preaching of Ustadzah Mumpuni Handayayekti in giving a lecture in Salaman Magelang uses a delivery method without preparation, namely taking material points using a clear voice and with the characteristics of Ustadzah Mumpuni Handayayekti's voice. Ustadzah Mumpuni Handayayekti's body language style in delivering a lecture in Salaman Magelang helps explain and emphasize the material delivered by Ustadzah Mumpuni Handayayekti to the listeners of the preaching.